Definitions of Computer-Assisted Surgery and Intervention, Image-Guided Surgery and Intervention, Hybrid Operating Room, and Guidance Systems: Strasbourg International Consensus Study. Issue 2 (20th December 2020) - Giménez, Mariano; Gallix, Benôit; Costamagna, Guido; Vauthey, Jean-Nicolas; Moche, Michael; Wakabayashi, Go; Bale, Reto; Swanström, Lee; Futterer, Jürgen; Geller, David; Verde, Juan M.; García Vazquez, Alain; et al.
Abstract : Objective: To develop consensus definitions of image-guided surgery, computer-assisted surgery, hybrid operating room, and surgical navigation systems. Summary Background Data: The use of minimally invasive procedures has increased tremendously over the past 2 decades, but terminology related to image-guided minimally invasive procedures has not been standardized, which is a barrier to clear communication. Methods: Experts in image-guided techniques and specialized engineers were invited to engage in a systematic process to develop consensus definitions of the key terms listed above. The process was designed following review of common consensus-development methodologies and included participation in 4 online surveys and a post-surveys face-to-face panel meeting held in Strasbourg, France. Results: The experts settled on the terms computer-assisted surgery and intervention, image-guided surgery and intervention, hybrid operating room, and guidance systems and agreed-upon definitions of these terms, with rates of consensus of more than 80% for each term. The methodology used proved to be a compelling strategy to overcome the current difficulties related to data growth rates and technological convergence in this field. Conclusions: Our multidisciplinary collaborative approach resulted in consensus definitions that may improve communication, knowledge transfer, collaboration, and research in the rapidly changing field of image-guided minimally invasive techniques. Abstract : This study gathered experts with multiple backgrounds and used common consensus-development methodologies in 2 phases (online and panel meeting). It resulted in definitions that may improve communication, knowledge transfer, collaboration, and research in the field of image-guided minimally invasive techniques.